2009
DOI: 10.1590/s0036-46652009000400003
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and association of HIV-1 non-B subtype with specific sexual transmission risk among antiretroviral naïve patients in Porto Alegre, RS, Brazil

Abstract: In South Brazil the circulation of two HIV-1 subtypes with different characteristics represents an important scenario for the study of the impact of HIV-1 diversity on the evolution of the HIV-1 epidemic and AIDS disease. HIV-1 B, the predominant variant in industrialized countries and HIV-1 C, the most prevalent subtype in areas with rapid epidemic growth, are implicated in most infections. We evaluated blood samples from 128 antiretroviral (ARV) naïve patients recruited at entry to the largest HIV outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 20 publications
3
20
2
3
Order By: Relevance
“…In terms of molecular diversity, our results corroborate previous studies that also reported a large dominance of subtype C (ϳ65%) in SC state (30)(31)(32)(33) and a more diverse epidemic in RS state, mainly because of the high prevalence of BC mosaic forms in the latter (ϳ25%) (34)(35)(36). In both states, a low prevalence of subtype F1 and BF1 recombinants (ϳ3%) was observed, while this frequency can reach up to 20% in northern regions of Brazil (37,38) and 40% in Argentina (39).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In terms of molecular diversity, our results corroborate previous studies that also reported a large dominance of subtype C (ϳ65%) in SC state (30)(31)(32)(33) and a more diverse epidemic in RS state, mainly because of the high prevalence of BC mosaic forms in the latter (ϳ25%) (34)(35)(36). In both states, a low prevalence of subtype F1 and BF1 recombinants (ϳ3%) was observed, while this frequency can reach up to 20% in northern regions of Brazil (37,38) and 40% in Argentina (39).…”
Section: Discussionsupporting
confidence: 91%
“…The similar curve of AIDS incidence in HET and the association of HIV-1C infections with this group indicate that the HIV-1C epidemic in Brazil might have been propelled by heterosexual transmissions. Although our sampling data did not find a segregated epidemic in RS, other studies with samples from the early 2000s did (35,36,44), which supports that in RS, HIV-1C also disseminated mainly among HET in the past. In fact, in Porto Alegre (capital city of RS), a study reported that the prevalence of HIV-1C significantly increased in HET but also subtly increased in MSM in the period from 1998 to 2008, while at the same time, the prevalence of HIV-1B significantly decreased in both groups (43).…”
Section: Discussionsupporting
confidence: 67%
“…Subtype B was detected in 22.6% of the patients, followed by CRF_31BC in 23.4%, subtype F in 10% and other mosaic forms in 5.5% 13 .…”
Section: Discussionmentioning
confidence: 96%
“…3,4,7,14,[19][20][21] No presente trabalho, a elevada prevalência do subtipo C e da CRF31_BC foi observada também no município de Canoas, com freqüências ainda mais elevadas (de 43,8% e 35,0%, respectivamente) do que em outros locais do estado. Foram ainda encontrados os subtipos B e F (18,8% e 2,4%, respectivamente), não tendo sido observados outros subtipos.…”
Section: Discussionunclassified
“…Resultado similar foi observado em estudo prévio realizado no município de Porto Alegre que, no entanto, reporta associação da disseminação do subtipo B com a prática sexual anal e, indiretamente, maior taxa de transmissão das outras variantes por intercurso vaginal. 7 Por outro lado, a observação de que o uso de drogas injetáveis aparece com maior freqüência entre os subtipos C e CRF31_BC e com alta prevalência entre os homens (25,6%) levanta a possibilidade da disseminação de tais subtipos entre mulheres por "populações pontes". Isso porque não ocorre diferença de freqüência dos subtipos entre os sexos, nem entre práticas sexuais, e a maioria das mulheres refere práticas heterossexuais e não é usuária de drogas injetáveis.…”
Section: Discussionunclassified